Arbitrator's misconduct in receiving evidence in arbitration proceedings - Mohd. Subha, Nurul Aishatul Adha (2011)
In arbitration, an arbitrator is the sole judge of the quantity and quality of evidence. He has to verify the admissibility and weight of the evidence. Besides, an award will normally be set aside, rather than remitted where there has been a serious miscarriage of justice affecting the evidence and the arbitrator cannot reasonably be expected to be able to approach the matter afresh. However the mere fact that the arbitrator has decided the case on undisclosed evidence is not enough. His award must be based on the evidence adduced at the hearing. It is part of his duty to determine matters of both of fact and of law. When conducting arbitration proceedings, an arbitrator must evaluate all the evidence before him when deciding on the issues that have been put before him. Failure by arbitrator to hear properly admissible evidence during proceeding will amount to misconduct and it is one of the basic grounds to challenge the arbitral award. Misconduct covers any action contrary to the principles of natural justice, which require that no man may be a judge in his own cause, and that every party has a right to be heard and to challenge any statement or document prejudicial to his case. Thus, this study intends to identify the circumstances that lead to misconduct by arbitrator in receiving admissible evidence which can be challenged in arbitral award. This study is carried out mainly through literature review and documentary analysis of law journals, such as Malayan Law Journal, Building Law Report, etc. The analysis showed that there were five main circumstances on arbitrator’s misconduct in receiving admissible evidence which include failure to analyse and appraise material and relevant evidence, misconstrued some relevant provision that were material, ignored material and relevant evidence, matters of public policy and hearing evidence of one party in the absence of the other. Most of the factors interpreted arbitrator’s misconduct where he failed to act fairly and impartially, failed to decide all issues and make the award, lack of understanding basic principles of evidence and lack of understanding the rules of evidence. Therefore, this study will be able provide a better guideline for the disputant parties in construction industries to be given a fair and judgement during the arbitration proceedings